Comparison of survival and progression after focal- or whole brain radiotherapy in patients with primary CNS lymphoma: results from a large multicenter analysis of the German Society of Radiation Oncology’s Neuro-Radio-Oncology Working Group (DEGRO AG-NRO) - Heider, Sina; Allwohn, Luisa; Rühle, Alexander; Ehret, Felix; Kaul, David; Oertel, Michael; Pepper, Niklas B.; Hoffmann, Elgin; Bodensohn, Raphael; Ruder, Arne Mathias; Popp, Ilinca; Merten, Roland; et al. (Radiotherapy and oncology, 2025)
Background and purpose - Primary central nervous system lymphoma (PCNSL) is a rare but aggressive disease. The application of radiotherapy (RT) as part of treatment usually involved whole-brain radiotherapy (WBRT). Focal radiotherapy (fRT) might be locally active, but comparative outcome data is lacking. - Materials and methods - Data from a multicenter registry of the German Society of Radiation Oncology’s Neuro-Radio-Oncology Working Group (DEGRO AG-NRO) was analyzed. Patients treated for PCNSL between 2007 and 2023 who received RT at any stage of their disease were included. Kaplan-Meier and Cox proportional hazards regression analyses were conducted to compare survival between focal (fRT) and whole-brain radiotherapy (WBRT). - Results - Survival data of 151 patients from eight centers were available. The median age at diagnosis was 66.5 years, and the median Eastern Cooperative Oncology Group Performance Status Scale (ECOG PS) was 2. Eighteen percent of patients (n = 27) received primary RT, 33 % (n = 49) consolidation RT, and 49 % (n = 73) RT for recurrent disease. Median overall survival (OS) from diagnosis was 24.1 months (95 % CI: 14.7-33.4), and median survival after RT was 7.2 months (95 % CI: 4.5-10.0). In patients treated with fRT (n = 28) median OS was 67.6 months (95 % CI: 35.7-99.6) compared to 20.1 months after WBRT (n = 123, 95 % CI: 10.5-29.8) (HR = 0.5, p = 0.016). Median survival after RT was also longer with fRT (44.0 months, 95 % CI: 5.9-82.1) than with WBRT (5.8 months, 95 % CI: 3.2-8.4) (HR = 0.5, p = 0.017). In recurrent disease median PFS after use of fRT was 3.8 months, compared to 3.0 months after WBRT (p = 0.164). After fRT, in 16/28 (39 %) patients tumor progression was observed (2/16 in-field, 3/16 out-field, 3/16 mixed, 8/16 unknown). In multivariate Cox-regression analysis, histology other than diffuse large B-cell lymphoma (HR = 0.345, p < 0.01) and fRT (HR = 0.518, p < 0.05) remained independently associated with improved OS. - Conclusion - fRT may be a beneficial treatment option for patients with PCNSL and needs to be studied further in prospective clinical trials.
Online verfügbar: 7. Juni 2025, Artikelversion: 17. Juni 2025
Gesehen am 18.08.2025